Implementation and Optimization of a CFD Solver Using Overlapped Meshes on Multiple MIC Coprocessors - Ma, Wenpeng; Hu, Xiaodong; Yuan, Wu (Scientific programming, 2019)
In this paper, we develop and parallelize a CFD solver that supports overlapped meshes on multiple MIC architectures by using multithreaded technique. We optimize the solver through several considerations including vectorization, memory arrangement, and an asynchronous strategy for data exchange on multiple devices. Comparisons of different vectorization strategies are made, and the performances of core functions of the solver are reported. Experiments show that about 3.16x speedup can be achieved for the six core functions on a single Intel Xeon Phi 5110P MIC card, and 5.9x speedup can be achieved using two cards compared to an Intel E5-2680 processor for two ONERA M6 wings case.